Le passage de la frontière - Claude François Baudez (Ateliers d'Anthropologie)
For three ethnic groups that practiced capture war (Aztecs, Iroquois and Tupinamba), the ritual that started with capture and continued beyond the execution served to assimilate the prisoner with his conqueror, the Other with the Self. Various steps in this transformation are seen as various moments of the crossing of a thick boundary. Whereas this boundary can only be permanently crossed through the execution of the captive, the steps that precede it present him as a person with an ambiguous status, both enemy and parent, hostile and impotent.